Effect of plant age and stress on flowering in litchi (Litchi chinensis) (Current Horticulture, 2024)
The experiment was conducted on eight year-old litchi (Litchi chinensis Sonn.) cv. Shahi at ICAR-NRC on Litchi, Muzaffrapur, Bihar during 2017-18. The results showed that trees started opening of flowers (male, hermaphrodite functionally female and hermaphrodite functionally male) on 4, 11 and 16 March 2017, and 11, 17 and 24 March 2018 respectively, whereas, in 15 year-old trees, anthesis of male, hermaphrodite functionally female and hermaphrodite functionally male was earlier on 1, 7 and 13 March 2017, and 7, 14 and 20 March 2018, respectively. Similarly, eight-year-old plant of Longia started opening of flowers (male, hermaphrodite functionally female and hermaphrodite functionally male) on 19, 27 and 30 March 2017, and 22, 30 March 2018 and 1 April 2018, respectively and 15 year-old trees started opening of flowers on 14, 21 and 25 March 2017 and 18, 25 and 29 March 2018, respectively. The eight year old Kasba plants located near road side were recorded with anthesis of flowers (male, female and hermaphrodite male flowers) on 12, 17 and 23 March 2017, and 16, 20 and 24 March 2018, respectively, whereas, 15-year old Kasba plant located at the centre of the field started opening of flowers on 15, 19 and 22 March 2017 and 20, 24 and 27 March 2018, respectively.
Keywords: Anthesis; Cultivars; Female flowers; Hermaphrodite flowers; Male flowers